Effect of Isoniazid Preventive Therapy on the Incidence of Tuberculosis among Seropositive Children Attending HIV/AIDS Care in Two General Hospitals, Northwest Ethiopia, 2021 - Fassikaw Kebede; Birhanu Kebede; Tsehay Kebede; Melaku Agmasu (Journal of Tropical Medicine)
The human immune deficiency virus (HIV) is the strongest risk factor for the incidence of tuberculosis (TB) by way of reactivation of latent or new infection. The provision of isoniazid preventive therapy (IPT) is one of the public health interventions for the prevention of TB. To date, there have been limited clinical data regarding the effectiveness of isoniazid preventive therapy (IPT) on TB incidence. This study aimed to assess the effect of isoniazid preventive therapy on the incidence of tuberculosis for seropositive children in Northwest Ethiopia. Methods. A facility-based retrospective follow-up was employed for reviewing 421 files from 1 January 2015 up to 30 December 2019. EpiData version 3.2 and Stata/14 software were used for data entry and analysis, respectively. Categorical variables at bivariable Cox regression were assessed for candidates transferred at P value <0.25 for multivariable Cox regression to claiming predictors associated with TB incidence rate at 95% CI at P<0.005. Result. The overall incidence of TB was found to be 4.99 cases per 100 person-years at 95% CI (3.89–6.53). Missed IPT (AHR = 7.45, 95% CI: 2.96, 18.74, P<0.001), missed cotrimoxazole preventive therapy (CPT) (AHR = 2.4, 95% CI: 1.84–4.74, P<0.022), age ≥ 11 years (AHR = 4.2, 95% CI: 1.04–7.03, P<0.048), MUAC ≤ 11.5 cm (AHR = 4.36, 95% CI: 1.97–9.97, P<0.001), WHO stages III and IV (AHR = 2.04, 95% CI: 1.12–3.74, P<0.022), and CD4 count ≤100 cells/μl (AHR = 3.96, 95% CI: 1.52–10.34, P<0.005) were significantly associated with TB incidence. Conclusion. Concomitant administration of ART with IPT had demoted more than ninety-six percent of new TB incidences for this report. Undertaking in-depth TB screening and frequent follow-up among all these children is critical in order to prevent and control tuberculosis.